Analisis Faktor-Faktor yang Mempengaruhi Kinerja Petugas Aviation Security (AVSEC): Studi Pengaruh Disiplin Kerja, Pengawasan, dan Motivasi - Bagus Hidayat Cahyo Ramadhan Hariyadi; Sundoro (MAN Insan Cendekia Jambi, 2025)
The performance of Aviation Security (AVSEC) personnel represents a critical element in ensuring flight safety within airport environments. This research aims to evaluate the extent to which Work Discipline, Supervision, and Work Motivation influence AVSEC Officer Performance. Employing a qualitative approach through literature review, the analysis examines literature from various scientific journals obtained through Google Scholar. Theoretically, research findings demonstrate that these three variables, Work Discipline, Supervision, and Work Motivation, exert positive and significant influence on AVSEC Officer Performance, both individually and collectively. These findings reinforce the importance of implementing comprehensive human resource management strategies, encompassing discipline enforcement, leadership strengthening, and creation of supportive work environments, to enhance overall AVSEC effectiveness and professionalism.